A Linguistic Study on Arab-Tamil “Arwi” - Zunoomy, Muhammadu Sainulabdeen; Safan, Sinna Lebbai Mohamed; Shathifa, Mohammed Cassim Sithy; Razick, Abdul Majeed (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2026)
Arwi, or Arabu-Tamil, is a unique writing system that uses Arabic phonetics to represent the Tamil language and has been a significant topic for linguistic and cultural research among Muslim communities in South India and Sri Lanka. This study aims to explore the nature of Arwi, examine whether it can be classified as an independent language or a dialect, and review its role in preserving the cultural and religious identity of Tamil Muslims. The research employs a historical-descriptive method, analyzing secondary sources including books, academic articles, and digital archives, alongside historical manuscripts and documents. The findings indicate that Arwi represents a blend of two traditional literary languages, Arabic and Tamil, serving as a written communication system for Tamil Muslim communities. Lacking an independent grammatical structure typical of a full language, Arwi is more accurately classified as a written dialect or specialized writing system rather than a standalone language. Nevertheless, it has played a crucial role in Islamic literature, religious education, and the preservation of cultural identity over centuries. The study emphasizes the importance of revitalizing Arwi through manuscript publication, educational inclusion, and everyday usage to safeguard this unique linguistic and cultural heritage.